Handling of expert knowledge in software product lines development with usage of repertory grids method - Gamzayev, Rustam O.; Tkachuk, Mykola V.; Shevkoplias, Daria O. (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2020)
The development of software product lines (SPL) is a promising way to create competitive software for the modern IT - market. Because of perpetual changes in user needs and the appearance of new software and hardware components for SPL, maintaining a certain level of variability at all stages of their full life cycle (FLC) becomes an actual problem. One of the most important stages is requirements engineering. To support this process it is advisable to utilize the methods of expert knowledge elicitation and analysis. Based on the recognized multilevel approach to SPL engineering proposed by K. Pohl, the research goal is to develop an approach to correct specification of variability features at the initial stages of SPL FLC. The analysis of methods to extract and process the expert knowledge is carried out, their classification is presented, and the method of repertory grid (RG) is chosen for the further usage. It allows analyzing and structuring expert knowledge in a multidimensional information space and makes it possible to consider various contextual factors that affect relevant requirements for the target SPL. The essentials of the RG method are considered and its formal description is elaborated. The examples of its usage in designing ​ “Smart House” systems which allow analyzing the technical, social and economic aspects of user requirements for software and hardware variability at the conceptual design stage of these systems are considered. As the result, a possibility to automate a process of a corresponding FODA-model creation is shown. That provides variability support at the next FLC stages of such systems.